A Systematic Indoor and Outdoor Study of the Effect of Particle Size and Concentration of TiO2 in Improving Solar Absorption for Solar Still Application - Samneang, Heng; Kumar, Laveet; Zafar, Amad; Ali, Muhammad Umair; Zahid, Taiba; Bibi, Saira; Ahmad, Muhammad Shakeel; Ghafoor, Usman; Selvaraj, Jeyraj (Frontiers in Materials, 2021)
Solar light absorber surface is probably one of the most important components in solar still that dictates the distillate yield. In this work, a systematic study has been conducted to investigate the effect of particle size and concentration of titanium oxide (TiO2) in black paint to increase the solar still absorber surface temperature. The various available particle sizes, i.e., 20nm, 150nm, and 400nm, have been mixed in black paint with varying concentrations and are applied on the absorber plate. XRD has been used for phase identification of as-received powders. UV-Vis spectroscopy has been used to examine light absorption properties. Finally, extensive indoor testing (using an improvised solar simulator) and outdoor testing have been conducted to optimize the concentration. An increase in surface temperature has been observed with the introduction of TiO2 nanoparticles in black paint. Furthermore, the increase in particle size leads to an increase in temperature. The highest surface temperature of 104.86oC, 105.42oC, and 106.32oC have been recorded for specimens with particles sizes 20nm (at 15wt% concentration), 150nm (at 10wt% concentration) and 400nm (at 7wt% concentration), respectively. Furthermore, the highest temperature of 69.69oC has been recorded for TiO2-400nm specimens under outdoor conditions, which is 15.97% higher compared to the bare aluminum plate. The increase in surface temperature may be due to high UV absorption. Moreover, an increase in particle size leads to high light scattering ability, further improves the light-harvesting ability.